Design and Experiment of a Differential-Based Power Split Device. (15th April 2014) - Zeng, Xiaohua; Peng, Yujun; Song, Dafeng; Zheng, Shuai; Wang, Zhongda; Yang, Nannan
Abstract : Hybrid electric vehicles have excellent energy efficiency and emission performance. Power split device (PSD) is a key component that directly affects the control strategy of power systems, the economic consumption of fuel, and the dynamic performance of vehicles. A differential-based PSD was proposed in this paper. A traditional differential was taken as the prototype and a new design method is proposed to retrofit the differential into a PSD. First, a comprehensive approach that includes theoretical analysis and software simulation was used to analyze the possibility as well as the necessity of retrofitting the differential into PSD. Then the differential was retrofitted. Finally, finite element analysis and bench test were conducted. Results showed that applying the retrofitted differential as PSD is practicable.